Effects of preseason climate change on spring and summer phenological shifts in Inner Mongolian grasslands - Nie, Zexu; Wang, Chao; Zhang, Na (Frontiers in Ecology and Evolution, 2024)
Grassland vegetation phenology has undergone great changes under the influence of climate, which affects ecosystem functions and services. However, the mechanism of preseason climatic factors in driving phenological shifts is unclear. In this study, we determined the start (SOS) and peak (POS) of the growing season for Inner Mongolian grasslands using gross primary productivity data (2000–2018). We investigated the spatiotemporal changes of SOS and POS and elucidated the mechanisms behind these changes by analyzing how these phenological events were influenced by the specific preseason climatic requirements (precipitation, air temperature, and solar radiation). Our results revealed that the SOS significantly advanced at a rate of 0.65 days/a, while the POS was stable across the study area. At the pixel scale, areas with initially later SOS and POS exhibited stronger advanced trends. An earlier SOS and POS were associated with lower thermal requirements, including air temperature and solar radiation. Conversely, a delayed SOS and POS necessitated higher climatic requirements. The impact of preseason precipitation on both SOS and POS demonstrated notable spatial variability. Moreover, the effects of different climatic factors on phenology were not in sync due to regional environmental disparities. Our study provides insight into the mechanisms underlying phenological shifts in grassland ecosystems under climate change.